ẢNH HƯỞNG CỦA NATRI CACBONAT, NATRI MOLIPDAT, CÁC ION KẼM VÀ PHỐT PHÁT ĐẾN SỰ ỨC CHẾ ĂN MÒN THÉP CACBON TRONG HỆ THỐNG NƯỚC LÀM MÁT - Huy, Vũ Đình; Tâm, Lưu Hoàng (Vietnam Journal of Chemistry, 2012)
Effects of sodium carbonate, sodium molybdate and synergistic combination of zinc and phosphate ions on the carbon steel corrosion inhibition in cooling water systems at room and 60oC temperatures have been investigated by mass loss and electrochemical methods. Sodium carbonate and sodium molybdate were added in concentrations from 100 to 500 ppm. Mixture of phosphate and zinc ions added with concentrations from 5 to 100 ppm by volume. The steel sample was evaluated by mass loss measurements after 4, 8, 24, 48, 72, 120, 144 and 168 hours of immersion at the room temperature and after 8 hours of immersion at 60oC. Based on the experiment results, steel corrosion inhibition mechanism was discussed and optimal concentration of corrosion inhibitors was determined and suitable conditions in order to use in practice.